Costruire ponti per ri-narrare identità di uomini e di città - Costanzo, Giovanna (B@belonline, 2021)
Narrative identity is perhaps the most well-known concept of Ricœuran investigation. In the dialectic between subjectivity and otherness, between activity and passivity, the narrative offers an opportunity to sew the tears between self and the many relationships that constitute us. Narrating to quell tensions and to resolve misunderstandings, ‘build texts’ to find in the ‘written’ words as in the ‘said’ words poetic suggestions and solutions to the many problems afflicting peoples. Writing stories that you can ‘read’ as stories of fatigue but also rebirth. So Ricœur tries an interesting connection between narration and architecture, between the identities of a people and the features of a city. Being able to read cities as texts means ‘seeing’ the space of the city understood as a metaphor of a complex identity, in which diversity compromises and alters the very status of the subject, which often needs to be said and narrated so as not to get lost completely.